Sintesis Kitosan Nanopartikel dengan Metode Sonokimia, Gelasi Ionotropik, dan Kompleks Polielektrolit - Talu’mu, Marlina Daeng (Jurnal Progres Kimia Sains, 2011)
The aims of this research are to find out how to prepare chitosan nanoparticles bysonochemical method; ionotropic gelation; and polyelectrolyte complexes and the influenceof variations in methods of perparation of chitosan nanoparticles to chitosan nanoparticlescharacteristics that include particle size dan functional group. Techniques of data collectionwas conducted by means of the observation of characteristics of chitosan nanoparticles. Theresults shows that the variation of the method of making an impact on the characteristics ofchitosan nanoparticles preparation. The particle size of nanochitosan synthesized bysonochemical, ionotropic gelation, and polyelectrolyte complex is 800, 500, 600 nm,respectively. Analysis of functional groups of chitosan nanoparticles by FTIR shows theabsorption characteristic spectrum of the nanochitosan.